The Influence of Flexible Working on Happiness at Work Through Employee Enggagement in Indonesia Financial Service Authority - Ferino Firmansah; Pantius Drahen Soeling (Dinasti International Journal of Education Management And Social Science, 2025)
Flexible Working Arrangement (FWA) is increasingly recognized as a strategic approach to improve employee well-being, particularly in public sector organizations that often struggle with rigid bureaucratic systems. This study investigates the direct and indirect effects of FWA on Happiness at Work (HAP), with Employee Engagement (EE) as a mediating variable. Using a quantitative approach, data were collected from 800 employees in the Indonesian public sector through a structured questionnaire. Structural Equation Modeling with SmartPLS 3.4 was used to test the hypotheses. The results showed that FWA significantly affected EE (? = 0.332, t = 5.504, p = 0.000) and HAP (? = 0.143, t = 2.742, p = 0.006). In addition, EE has a strong positive effect on HAP (? = 0.530, t = 10.868, p = 0.000) and significantly mediates the relationship between FWA and HAP (indirect effect ? = 0.176, t = 5.516, p = 0.000). These findings underscore the importance of fostering a flexible work environment to enhance employee engagement and psychological well-being.